Ecological Perspective on Health Promotion : Systems, Settings and Social Processes. - Samdal, Oddrun; Samdal, Oddrun (SAIF Zone : Bentham Science Publishers, 2012)
This e-book adds a new dimension to currently available text in health promotion by applying examples from evaluation studies to explore basic health promotion principles. It thus goes beyond single case study descriptions. The volume intricately blends an ecological approach with social science.A multiple settings approach is extensively covered by analyzing participants' perceptions of the family, leisure and school settings. Chapters of this volume also present intervention data aiming at promoting participants' perceptions and empowerment in the settings. Furthermore, the e-book covers several topic areas central to health promotion, such as life satisfaction, health behaviours (tobacco, physical activity) and health complaints and body image. Another central principle in health promotion, namely development of healthy public policy is covered including descriptions about how health promotion policies are influenced by national and international political developments. This historical perspective adds to the current knowledge of how to establish and develop policies as a basis for all health promotion actions.
01 Title.pdf -- 02 Cover Page -- 03 REVISED eBooks End User License Agreement-Website -- 04 Contents -- 05 Foreword -- 06 Preface -- 07 List of Contributors -- 08a Part 1 -- 08b Chapter 01 -- 09 Chapter 02 -- 10 Chapter 03 -- 11 Part 2 -- 12 Chapter 04 -- 13 Chapter 05 -- 14 Part 3 -- 15 Chapter 06 -- 16 Chapter 07 -- 17 Chapter 08 -- 18 Part 4 -- 19 Chapter 09 -- 20 Chapter 10 -- 21 Subject Index.
Bentham Science Open Access Books
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2017. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Health education -- Planning; Health promotion; Health promotion; Electronic books